2003
DOI: 10.1556/aagr.51.2003.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Response of two sunflower hybrids to planting dates and densities

Abstract: This investigation was carried out at the Experimental Farm of Assiut University during the summers of 2000 and 2001 to study the responses of two sunflower hybrids (Vidoc and Euroflora) to planting dates (May 1 st , June 1 st and July 1 st ) and planting densities (55,533, 83,300 and 166,600 plants/ha). The results indicated that the two varieties differed highly significantly in all studied traits except oil yield/ha. The highest seed yield (3.64 t/ha) was obtained with the variety Vidoc. In addition, the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 1 publication
4
17
0
Order By: Relevance
“…This may be due to the sufficient of environmental conditions in wide spacing and less competition between plants as well as increase light penetration within plant canopy which increased assimilation rate and oil formation. These results are in a good line with those obtained by Yakout et al, (1992), Sharief (1998), Allam et al, (2003), Ruffo et al, (2003), Ali and Osman (2004), And Tenebe et al, (2008). The sowing density and different nutrient levels had exerted a significant positive influence on seed yield of sunflower.…”
Section: Yield Parameters and Seed Yield (Tables 3 And 4)supporting
confidence: 90%
“…This may be due to the sufficient of environmental conditions in wide spacing and less competition between plants as well as increase light penetration within plant canopy which increased assimilation rate and oil formation. These results are in a good line with those obtained by Yakout et al, (1992), Sharief (1998), Allam et al, (2003), Ruffo et al, (2003), Ali and Osman (2004), And Tenebe et al, (2008). The sowing density and different nutrient levels had exerted a significant positive influence on seed yield of sunflower.…”
Section: Yield Parameters and Seed Yield (Tables 3 And 4)supporting
confidence: 90%
“…The increase in plant sowing density has also caused stress in plants, resulting early flowering and physiological maturity. The results of current study are agree with those reported by Esechie et al (1996); Allam et al (2003) and Ibrahim and El-Genbehy (2009). The head diameter, number of seeds in a head and thousandseed weight which are considered as the main yield criteria, which were affected by the change in interrow and intra row spacings.…”
Section: Resultssupporting
confidence: 93%
“…However, with plant density increases, the competition for light between plant increases, which result in the decrease in vegetative and reproductive plasticity of plant [5], while a lower plant density, results in a decreased absorption of light by the plants, as well as decrease in crop yield per unit area [6,7]. Theoretical research and practical experience have shown that the high yield per unit area is usually associated with low competitiveness among plants [8,9], while head diameter, plant biomass, 100-seed weight, seed yield per plant, non-saturated fatty acids, and seed oil percentage decreased with an increase in plant density [10].…”
Section: Introductionmentioning
confidence: 99%